Growth Profile and Fatty Acid Accumulation of Four Chaetoceros Taxa Isolated from Coastal Water of Pahang, Malaysia - Mohd Anuar, Mohd Fuad; Mohammad Noor, Normawaty; Khan Chowdhury, Ahmed Jalal; Yunus, Kamaruzzaman (Penerbit UKM, 2015)
This indoor study was aimed to analyze the production of fatty acids with their growth profile from few marine algae under the genus Chaetoceros isolated from coastal water of Pahang, Malaysia. The algae were established into culture using standard marine media (f/2 media) and the variation of fatty acid for each species was determined using GCMS. Statistical analysis of one-way ANOVA was performed to evaluate the significant and homogeneity data on the growth of each alga and total fatty acid percentage obtained. The results showed that four taxa were successfully cultivated and identified as Chaetoceros baculites, Chaetoceros anastomosans, Chaetoceros affinis var. willei and Chaetoceros affinis var. affinis. Out of four Chaetoceros, C. baculites showed the highest growth rate (0.75 cell.day-1) and division’s value (1.08) while C. anastomosans showed the highest doubling time value (8.66). Statistical analysis showed that all species have significantly different growth rate (p<0.05). Myristic acid was the main component for fatty acid storage for C. baculites, C. anastomosans and C. affinis var. willei whereas palmitic acid for C. affinis var. affinis. All species contained about 35 to 75% of total percentage fatty acids throughout the growth day. Based on total percentage, both affinis varieties had high fatty acid percentage compared with the other two species with the total percentage of more than 70%. As a conclusion, all four taxa are suitable to be used in lipid industry in Malaysia with C. affinis var. affinis is the best candidate for bio-fuel industry and C. anastomosans for pharmaceutical industry.